2005
DOI: 10.1074/mcp.m500078-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Gel-separated Proteins and Their Phosphorylation Sites by LC-MS Using Unlabeled Internal Standards

Abstract: Protein phosphorylation plays a critical role in normal cellular function and is often subverted in disease. Although major advances have recently been made in identification and quantitation of protein phosphorylation sites by MS, current methodological limitations still preclude routine, easily usable, and comprehensive quantitative analysis of protein phosphorylation. Here we report a simple LC-MS method to quantify gel-separated proteins and their sites of phosphorylation; in this approach, integrated chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
73
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 45 publications
1
73
0
Order By: Relevance
“…We and others have shown that the data in LC-MS and LC-MS/MS experiments have inherent quantitative information such that it is possible to use this type of data to assess protein amounts in cells and tissues (17)(18)(19). Although labelfree methods for quantitative proteomics based on spectral counts have been described (4,20,21), their level of precision only permits the use of spectral counts as an approximate indication of protein abundance (17).…”
mentioning
confidence: 99%
“…We and others have shown that the data in LC-MS and LC-MS/MS experiments have inherent quantitative information such that it is possible to use this type of data to assess protein amounts in cells and tissues (17)(18)(19). Although labelfree methods for quantitative proteomics based on spectral counts have been described (4,20,21), their level of precision only permits the use of spectral counts as an approximate indication of protein abundance (17).…”
mentioning
confidence: 99%
“…2B) with a signal-to-noise ratio, indicating that this approach allows for measuring signal transduction pathway activation with great sensitivity; the use of new generation commercial mass spectrometers, such as linear ion traps or Fourier transform ion cyclotron resonance instruments, should result in the achievement of even lower limits of detection. This sensitivity sharply contrasts with that afforded by currently used MS methods for the quantification of phosphoproteins in cells that require Ϸ10 7 -10 8 cells per experimental point (16,17,27).…”
Section: Resultsmentioning
confidence: 65%
“…This fact means that even the most sensitive mass spectrometers struggle to detect sites of modification on regulatory proteins (quantification being even more challenging). Thus, MS-based proteomic studies aimed at investigating the mechanisms of signal transduction have used large numbers of cells (typically Ϸ10 8 ) per data point (16,17,27), overexpressed the protein under study (18), or performed analyses on recombinant proteins (31). Clearly, these strategies are not applicable to the analysis of all biological specimens, and it is extremely challenging for current mass spectrometric methods to detect regulatory proteins and their sites of modification in clinically relevant tissues such as biopsies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Digestion of gel-immobilized proteins was performed as described in ref. 45 except that extracted Fig. 5.…”
Section: Methodsmentioning
confidence: 99%